Strategy Council Religious Study Raudhatul Paradise in Cultivating Moderate Religious Attitudes among Students - Solatul Aini; Muh. Zakaria (CV. Edujavare Publishing, 2026)
Indonesia is wrong one from many country which multicultural in world, this matter of course caused, because Indonesia is country which own diverse variety race, ethnicity, language, religion, and culture. Study This aim for analyze strategy Council Raudhatul Jannah Study Group Jontak in grow attitude moderation religious students in Danger Village. The research uses a descriptive qualitative approach. Data sources study consists of on data primary and data secondary. Collection Data collection was conducted through observation, interviews, and documentation. Data analysis used data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that the strategies implemented by Majlis Taklim Raudhatul Jannah were implemented through four main management functions: planning, organizing, actuating, and controlling. At the planning stage, program coaching designed with integrate. The values of religious moderation, such as tawassuth (religious tolerance), tawazun (compassion), i'tidal (compassion), and tasamuh (compassion). In the organizational stage, the Islamic study group (Majlis Taklim) involves administrators, religious teachers, community leaders, and guardians of students in the collaborative implementation of the program. The implementation stage is carried out through religious studies, habituation, role models, religious discussions, and social activities that encourage the internalization of the values of moderation in the students' lives. Meanwhile, monitoring and evaluation are carried out periodically to measure the development of students' attitudes and behavior and to increase the effectiveness of the development program. Thus, the implementation of an integrated Islamic boarding school management strategy can effectively foster an attitude of religious moderation among students.